Universal principles of architecture : 100 architectural archetypes, methods, conditions, relationships, and imaginaries - Frankowski, Nathalie; Garcia, Cruz, 1983-; WAI Architecture Think Tank. (2023)
"Universal Principles of Architecture is a concise, visual introduction to 100 of the most fundamental elements of architecture"--
Archetypes -- Methods -- Conditions -- Relationships -- Imaginaries.
Includes index.
Keywords: Architectural design; Architecture -- Composition, proportions, etc